Fungsi Komunikasi Islam dalam Perspektif Al-Qur’an : Analisis Keberfungsian Fungsi Menginformasikan dan Fungsi Sosialisasi - Yusri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This article aims to discuss the function of Islamic communication from the perspective of the Qur'an. The functions discussed here are the informing function and the socialization function. The functions discussed are directed at how to make these functions function as they should. In other words, these functions are not only discussed at a normative level, but also more importantly at an applied level. This discussion involves various critical studies of several related interpretations which are linked to the efforts to function of the Islamic communication function being discussed. From this study, it was found that the information function only works if all components in the information cycle are actually carried out as they should. The function of socialization will only truly function if the factors that influence a person's interest in socializing with other people are implemented properly in accordance with the guidance of Islamic religious teachings.